Pembelajaran Tahfidz Al-Qur’an Virtual di UIN Jakarta dan IIQ Jakarta - Lilik Ummi Kaltsum; Ahsin Sakho Muhammad (Refleksi, 2022)
This paper is the result of research that discusses virtual tahfiz al-Qur’an learning at the Syarif Hidayatullah State Islamic University Jakarta and the Jakarta Institute of Al-Qur’an Science. The problem in this paper is where the learning process is currently carried out in a virtual or online manner which has led to a different reception among academics. This paper also reviews some of the applications used in the tahfiz learning process. In addition, the purpose of this paper is to compare the application of virtual tahfiz al-Qur'an in several institutions to find the advantages and characteristics of each applied learning model. Thus, educational institutions must prepare learning strategies in the future in utilizing existing technology, as well as preparing students to be resilient to situations and conditions. So that virtual learning is considered effective.